Literacy Development at Camp: Leveraging Language Models. (18th March 2021) - Dostal, Hannah M.; Scott, Jessica A.; Weir, Joan; Kang, Ki Y.; Amadi-Ihebuzor, Chidinma; Bernard, Teri-Ann
Abstract: There is little research on effective educational experiences for deaf and hard‐of‐hearing (d/hh) children in Jamaica. Using a formative and design experiment framework, in this project we explored the potential efficacy of an intensive literacy camp that provided professional development for d/hh adults working in classrooms with d/hh children, and provided literacy instruction for elementary‐age campers. We found that the children improved in all tested areas, and observations of d/hh adults provided evidence that with minimal training they were able to implement important facets of literacy instruction with the campers. Further research on these types of experiences and their potential for lasting impact after the camp is necessary.